DEVELOPING A FOREST FIRE DISASTER MANAGEMENT SYSTEM USING GIS AND MACHINE LEARNING - Low, Dewon (Universiti Teknologi PETRONAS, 2020)
Forest is an essential element for a cycle of ecosystem, Malaysia own total country area approximately 33.03x10^6 hectare, the land area 32.86x10^6 hectare, agricultural area around 8.59x10^6 hectare, forest area covered 22.19x10^6 hectare proven by FOA. Due to the rapid growth in economy and population in developing countries, at the end of the result deforesting will be occur with activity conversion of rainforest to land-use and lead to open fire burning the chopped tree and plant due to lowest cost and fastest way to eliminate the unused of tree. The man-made forest fire disaster are occur due to minor mistake error, although most of the southern east-Asia was peat swamp forest consider as moist forest among all other type of forest. However, the cause of forest fire may lead to negative impact on habitat and critical infrastructure therefore spatial and attribute data of impact on habitat and critical infrastructure are require to improve by develop Spatial Decision Support System (SDSS) of forest fire management and evaluate the possible impact of forest fire on habitat and infrastructure.